2023
DOI: 10.1108/jmp-04-2022-0183
|View full text |Cite
|
Sign up to set email alerts
|

Occupational self-efficacy, job crafting and job satisfaction in newcomer socialization: a moderated mediation model

Abstract: PurposeDrawing on job crafting theory and the social cognitive theory of work satisfaction, the purpose of this study is to examine the impacts of task, relational and cognitive crafting on job satisfaction and how occupational self-efficacy (OSE) and hierarchical organizational culture affect the execution and outcome of job crafting behaviors.Design/methodology/approachData were collected at four time points among Chinese media professionals (N = 198) during three consecutive months. Regression analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…This is since problem-solving skills and self-managerial skills are closely associated and may affect one another [12]. Effective problem-solving requires strong self-managerial skills such as self-motivation, time management, and self-regulation, while developing problem-solving skills can also help improve self-managerial abilities [13,14]. To enhance good self-managerial skills by developing problem-solving skills in undergraduate students, a researcher found that there were a few gaps in this research area, which were that students should not only have skills of self-problem-solving but also skills of self-appraisal to run the process of evaluating one's performance.…”
Section: Introductionmentioning
confidence: 99%
“…This is since problem-solving skills and self-managerial skills are closely associated and may affect one another [12]. Effective problem-solving requires strong self-managerial skills such as self-motivation, time management, and self-regulation, while developing problem-solving skills can also help improve self-managerial abilities [13,14]. To enhance good self-managerial skills by developing problem-solving skills in undergraduate students, a researcher found that there were a few gaps in this research area, which were that students should not only have skills of self-problem-solving but also skills of self-appraisal to run the process of evaluating one's performance.…”
Section: Introductionmentioning
confidence: 99%